Factores asociados al abandono de la lactancia materna: una revisión sistemática de alcance - Sigcho Valarezo, Valeria Lizbeth (2024)
Despite the recognized recommendation of the World Health Organization that exclusive breastfeeding should be the main source of nutrition for infants during the first 6 months of life, not all mothers follow this recommendation, choosing not to breastfeed totally or partially during this period. For this reason, the present study was designed to identify the factors associated with the abandonment of breastfeeding. The protocol was constructed based on the PRISMA ScR guidelines and the JBI manuals. The search for information was conducted in: PUBMEB, SciELO LILACS, Dialnet. Based on the use of descriptors and the Boolean AND computer. In relation to the results, 363 articles were identified, of which 12 articles were finally selected, and in them it could be evidenced that the main factors associated with the abandonment of breastfeeding are: low breast milk production, cracked nipples, mastalgia, use of bottles and pacifiers, return to work, incorporation into student life and lack of knowledge about the benefits of breastfeeding. In conclusion, the abandonment of breastfeeding is a multifactorial problem that was highlighted in the scientific evidence analyzed, where situations related mainly to the mother are strongly linked to the abandonment of breastfeeding